Korelasi Minat dan Hasil Belajar Siswa Melalui Penerapan Problem Solving Pada Materi Wujud Zat dan Perubahannya - Fatmalasari. L, Rizky; Latukau, Randi Hasim; Edi Saputra, I Gede Purwana; Permana, Imam; Kadir, Fitriani; Azmar, Azmar; Rahmat, Dedy (Al-Khazini, 2021)
This research is a descriptive study with a correlation type involving seventh grade students of SMP Negeri 3 Leihitu. Research variables, namely variables of interest in learning and achievement of physics learning outcomes, while the data analysis technique is descriptive analysis and inferential analysis with the correlation method. The results of this study prove that students' interest in learning provides a significant relationship with the achievement of learning outcomes in physics. The results illustrate that students' interest in learning who is taught using problem solving methods can affect student concentration in learning in order to achieve learning outcomes outcomes of physics. In using the problemsolving method, students think more and act creatively in solving problems, where the teacher involves more students as subjects who seek and solve on their own and not as objects that only receive information from the teacher, so that students can actively learn and appreciate knowledge. which theyreceive at school in order to develop their knowledge and skills